System for Mobile Monitoring of Vital Functions and Environmental Context. (2017) - Trobec, Roman; Avbelj, Viktor; Stanič, Uroš; Depolli, Matjaž; Rashkovska, Aleksandra; Tomašič, Ivan; Krištofelc, Tomaž; Bregar, Klemen; Kosec, Gregor
Abstract: The use of ICT in the health care system is aimed to increase efficacy and decrease costs. We have designed a system and services for mobile monitoring of vital physiological parameters and environmental context. The system is based on a small multi-functional wireless body sensor for simultaneous measurement of ECG, temperature, heart rate, respiration rate, and movement. The sensor is wirelessly connected through Bluetooth Smart to a Smartphone. When necessary, the measurements are transferred to a server and can be accessed by authorized personnel. The contribution of the system to improved quality and efficiency of medical care is validated and estimated through several pilot studies.